Endoscopic Balloon Dilatation as an Effective Treatment for Lower and Upper Benign Gastrointestinal System Anastomotic Stenosis. Issue 2 (April 2015) - Akarsu, Cevher; Unsal, Mustafa Gokhan; Dural, Ahmet Cem; Kones, Osman; Kocatas, Ali; Karabulut, Mehmet; Kankaya, Burak; Ates, Mustafa; Alis, Halil
Abstract : Objective: Endoscopic balloon dilatation (EBD) is currently accepted as an effective, safe, and first-line treatment of postoperative benign gastrointestinal anastomosis stenosis (BGAS); however, a limited number of publications on the subject exist in the literature. The aim of the study was to retrospectively evaluate the efficiency of endoscopic dilatation in patients with postoperative intestinal anastomotic stenoses at a single surgical center. Methods: Patients with postoperative BGAS treated by EBD at our institution from February 2008 to 2012 were included. The dilatations were all performed using through-the-scope balloons. The balloon was introduced into the stricture using a guidewire under radiologic guidance. Each dilatation session consisted of 2 to 3 two-minute multistep inflations of the balloon until adequate dilatation was achieved. Results: Of the 48 patients included in the study, 44 patients (91.7%) fully recovered and 4 (8.3%) did not respond to treatment. The mean follow-up period was 24 months (range, 3 to 57 mo). Four patients who did not respond to the procedure were treated surgically. Two patients (4.1%) with intestinal perforation during EBD were treated conservatively with a stent. Conclusions: EBD has a low rate of complications and a high success rate, is well tolerated, and avoids further surgical procedures for BGAS. Therefore, EBD should be the first choice of treatment for postoperative anastomotic stenoses.